Effectiveness of the fun for wellness online behavioral intervention to promote well-being and physical activity: protocol for a randomized controlled trial - Myers, Nicholas D. (BMC Public Health, 2019)
BACKGROUND: Fun For Wellness (FFW) is an online behavioral intervention developed to encourage growth in well-being by providing capability-enhancing learning opportunities to participants. Self-efficacy theory guides the conceptual model underlying the FFW intervention. Some initial evidence has been provided for the efficacy of FFW to promote: well-being self-efficacy; interpersonal, community, psychological and economic subjective well-being; and, interpersonal and physical well-being actions. The purpose of this paper is to describe the protocol for a new randomized controlled trial (RCT) designed to provide the first investigation of the effectiveness of FFW to increase well-being and physical activity in adults with obesity in the United States of America. METHODS: The study design is a large-scale, prospective, parallel group RCT. Approximately 9 hundred participants will be randomly assigned to the FFW or Usual Care (UC) group to achieve a 1:1 group (i.e., FFW:UC) assignment. Participants will be recruited through an online panel recruitment company. Data collection, including determination of eligibility, will be conducted online and enrollment is scheduled to begin on 8 August 2018. Data collection will occur at baseline, 30 days and 60 days after baseline. Instruments to measure demographic information, anthropometric characteristics, self-efficacy, physical activity and well-being will be included in the battery. Data will be modeled under an intent to treat approach and/or a complier average causal effect approach depending on the level of observed engagement with the intervention. DISCUSSION: The effectiveness trial described in this paper builds upon the 2015 FFW efficacy trial and has the potential to be important for at least three reasons. The first reason is based upon a general scientific approach that the potential utility of interventions should be evaluated under both ideal (e.g., more controlled) and real-world (e.g., less controlled) conditions. The second reason is based upon the global need for readily scalable online behavioral interventions that effectively promote physical activity in adults. The third reason is based upon the troubling global trend toward obesity along with evidence for obesity as a risk factor for several major non-communicable diseases. TRIAL REGISTRATION: ClinicalTrials.gov, identifier: NCT03194854, registered 21 June 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-019-7089-2) contains supplementary material, which is available to authorized users.